Automatic Hand Sanitizer Dispenser - Muhammad Imam Syahputra; Ummul Khair; Arnes Sembiring (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2021)
The development of technology in the IT field is currently growing rapidly and has become a benchmark in the development of human life. Technology has made work done by humans more efficient and less harmful to humans, especially in terms of maintaining health during the COVID-19 pandemic. Because there are still many people who directly touch the facilities provided in public places, such as hand sanitizers. This tool was built to prevent the spread of COVID-19 at this time and can implement social distancing. In the manufacture of this automatic hand sanitizer, ultrasonic sensors and a mini dc water pump are used. The use of ultrasonic sensors can minimize other people to directly touch the tools provided. The way this tool works is very simple, the first step taken is to bring the hand closer to the sensor with a vulnerable distance of 3cm to 5cm, if the sensor captures the object's signal from a predetermined distance, the pump will automatically pump the hand sanitizer out automatically. Keywords: Hand Sanitizer, Ultrasonic, Mini DC Water Pump, Arduino uno, COVID-19